KEBERANIAN RASULULLAH SAW DAN SAHABATNYA: ANALISIS PROSES PENELADANAN BERBASIS TEORI ITTIBA’ AN-NAHLAWY - Zulfatmi Budiman (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2018)
This article explore aboute the mettle of Rasulullah and his friend. The Qur'an is a book that has a very high spirituality, and the Prophet Muhammad is the most capable figure in translating the teachings of the Qur'an in all its attitudes and behaviors. Therefore, the whole attitude and behavior of the Prophet Muhammad is contained in spiritual values, among which is the value of courage. The position of the Prophet Muhammad saw as a hasanah makes his brave attitude as a model for his companions ra. The companions emulate the brave attitude of the Prophet Muhammad through ittiba 'process. It is a process of thinking of a believer who empowers the potential of the nafs, the 'aql and the qalb- and the potential of ruhaniyah -ruh and fithrah- the sacred, controlled and preserved of everything contrary to the spirit (spirit) divine teaching, so the association processKeywords: mettle; personage, and belief